Bridging contextual and individual factors of academic achievement: a multi-level analysis of diversity in the transition to higher education - Mikaël De Clercq; Benoît Galand; Virginie Hospel; Mariane Frenay (EARLI, 2021)
The transition to higher education has been extensively documented in the literature. In this line, many individual variables were identified as strong predictors of academic achievement. Yet, this literature suffers from one main limitation; contextual factors have often been left out of the investigation. The majority of studies have tested the impact of individual characteristics assuming that the effects are the same in different programs. However, differences between institutions or programs could result in specific learning contexts leading to different adjustment processes. As an attempt to overcome this limitation, the current study has investigated the impact of both individual and contextual factors on academic achievement through a multifactorial multilevel analysis. The analyses were carried out on 1,173 freshmen from 21 study programs. Results highlighted that 15% of variation in students' achievement was found between programs. Aspects of curriculum organization that contributed to academic achievement were gender ratio, opportunities given for practice and class size. Besides, seven individual factors were also predictive of academic achievement in the multifactorial approach: past performance, socioeconomic status, self-efficacy beliefs, value, mastery goal structure, study time and paid job. Finally, significant random effects were identified for peer support, course value, attendance and external engagement (i.e. commitment in extra-academic activities). The implications and limitations of this study are discussed. By connecting individual and contextual predictors of academic achievement this study intends to endorse a frontline approach regarding the transition to higher education.